Sick or rich: Assessing the selected soil properties and fertility status across the tea-growing region of Dooars, West Bengal, India - Malakar, Harisadhan; Timsina, Gagan; Dutta, Jintu; Borgohain, Arup; Deka, Diganta; Babu, Azariah; Paul, Ranjit Kumar; Yeasin, Md.; Rahman, Feroze Hasan; Panja, Saumik; Karak, Tanmoy (Frontiers in Plant Science, 2022)
Harnessing the potential yields of evergreen perennial crops like tea (Camellia sinensis L.) essentially requires the application of optimum doses of nutrients based on the soil test reports. In the present study, the soil pH, organic carbon (OC), available potassium as K2O (AK), and available sulphur (AS) of 7300 soil samples from 115 tea estates spread over the Dooars ranging from 88°52'E to 89°86'E longitude and 26o45'N to 27°00'N latitude of West Bengal, India have been documented. About 54% of soil samples were found within the optimum range of soil pH (4.50-5.50) for tea cultivation. The overall range of OC was found from 0.28% to 6.00% of which, 94% of the analysed samples were within the range of satisfactory to excellent level of OC i.e. (>0.80% to 6.00%). Around 36.3% of soil samples were found to have high AK (>100 mg kg-1) but 37.1% of soils were found to have high AS content (>40 mg kg-1). The nutrient index status of soil pH was low in Dam Dim, Chulsa, Nagrakata, Binnaguri, and Jainti sub-districts. Soils from five sub-districts had a high nutrient index (2.47 to 2.83) for soil organic carbon. However, it existed in the medium index (1.69 and 2.22) for Dalgaon and Kalchini sub-districts. Only Nagrakata sub-district soil samples were in the high nutrient index (2.65) for AK. All analysed samples showed a medium nutrient index (1.97 to 2.27) for AS. The result indicated that soil pH was significantly negatively correlated with soil OC (-0.336) and AK (-0.174). However, the soil OC was significantly positive correlated with AK (0.258) and AS (0.100). It could be concluded that a balanced fertilizer application would be needed as a part of the soil improvement program through soil chemical tests for sustainable tea cultivation.